2012
DOI: 10.1063/1.4709614
|View full text |Cite
|
Sign up to set email alerts
|

Separation of blood cells using hydrodynamic lift

Abstract: Using size and deformability as intrinsic biomarkers, we separate red blood cells (RBCs) from other blood components based on a repulsive hydrodynamic cell-wall-interaction. We exploit this purely viscous lift effect at low Reynolds numbers to induce a lateral migration of soft objects perpendicular to the streamlines of the fluid, which closely follows theoretical prediction by Olla [J. Phys. II 7, 1533, (1997)]. We study the effects of flow rate and fluid viscosity on the separation efficiency and demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 27 publications
3
42
0
Order By: Relevance
“…But there are few works where cell separation microdevices are solely designed based on the deformabilityinduced cross migration. For example, Geislinger et al 128 separated RBCs from other blood components by harnessing deformability-selective cell-wall interaction in a non-inertial flow inside a microchannel (Fig. 4(a)).…”
Section: Deformability-selective Cell Separationmentioning
confidence: 99%
“…But there are few works where cell separation microdevices are solely designed based on the deformabilityinduced cross migration. For example, Geislinger et al 128 separated RBCs from other blood components by harnessing deformability-selective cell-wall interaction in a non-inertial flow inside a microchannel (Fig. 4(a)).…”
Section: Deformability-selective Cell Separationmentioning
confidence: 99%
“…For a fixed shape, Uðk; r 1 ; r 2 Þ decreases with increasing viscosity ratio k. 26 This prediction has been shown to be in qualitative agreement with experiments and theoretical results for deformable lipid vesicles in microgravity 42,43 and for RBCs and platelets in a Poiseuille flow. 39 …”
Section: A Non-inertial Hydrodynamic Liftmentioning
confidence: 99%
“…The RBCs start a tank-treading motion when affected by the sheath flow. 39,45,47,48 This includes a stable inclination angle of the RBCs when passing x 1 and results in an entrance height of z RBC_x1 ¼ (8 6 2) lm. The centers of the cell distributions are already segregated with the RBCs below the melanoma cells while the distributions itself still overlap clearly.…”
Section: -4mentioning
confidence: 99%
“…Maenaka et al [32] demonstrated this size-dependent separation scheme for binary droplets in a pinched channel. Geislinger et al [33] exploited the separation of red blood cells from other blood components in a simple T-shaped channel. Using the same channel, sorting of the circulating MV3-melanama cells from suspension of red blood cells was also achieved [34].…”
Section: Introductionmentioning
confidence: 99%